Individual variability of higher mental functions in preschool children with regard to the material prosperity of the family (neuropsychological analysis) - M. S. Nerovnykh (Acta Biomedica Scientifica, 2024)
The problem of human individual development requires not just the accumulation and generalization of data, but also clarification, a systematic understanding of the individual variability of higher mental functions in relation to environmental factors and taking into account the risks associated with their formation.The aim: to identify systematic patterns of correlation between individual variability of higher mental functions of preschool children and the material prosperity of their families.Methods. Traditional neuropsychological tests developed by A.R. Luria and adapted in the neuropsychology laboratory of the Faculty of Psychology at Lomonosov Moscow State University were used. We examined 180 preschool children from families with high, average, and low income.Results. The greatest individual variability in the period of preschool age in relation to the level of material prosperity of the family, are the functions with a long period of formation, these are functions of block III of the brain, and the functions provided mainly by the left hemispheric parts of the brain. Children from the most affluent families have the highest indices of brain block  III functions (p  <  0.001) and left hemispheric functions (p < 0.001). Preschoolers from low-affluence families had indexes of both front brain function (p < 0.001) and left hemispheric function (p < 0.001) in the zone of negative values.Conclusion. The empirical results of the study allow us to clarify that the factor of material prosperity of the family, both directly, factor-wise, and indirectly, cumulatively, through the system of proximal factors, can make its selective contribution to the variability of indicators of children’s higher mental functions.